Changing girlhoods – Changing Girl Guiding. Issue 1 (January 2018) - Halls, Amy; Uprichard, Emma; Jackson, Clare
This article discusses the changing nature of girlhood over the last century as it is depicted through an empirical study of all editions of Girl Guide handbooks since 1910. The article describes three strands of change, which we describe as 'stringy', insofar as they are co-occur together and are difficult to untangle from one another; yet they are also stories of change that are nevertheless visible as strands in and of themselves through the empirical material. We illustrate the importance of incorporating children and childhood into more general theories of social change, in order to better understand how they are intrinsic to the mechanisms of intergenerational change.